PENGGILINGAN DAN PEMASARAN BAHAN JAMU TRADISIONAL DI KABUPATEN SUKOHARJO - Sudarmi Sudarmi; Maria Helena Sri Rahayu (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2015)
The purpose of community service on Small and Medium Enterprises (SME) Milling and Marketing bussines of Traditional Medicinal Materials in Sukoharjo are: 1) Increasing knowledge about hygiene in working with medicinal products. 2) Increased capacity and management skills such as bookkeeping and packaging capabilities. 3) Increasing the effectiveness of the production, by using the appropriate machine tool. Indicators of  success in science and technology applied to  "business" in the form of increase in the value of the post-test and increased production of ≥ 25%. Results devotion: 1) Based results of pre-test and post-test there is an increased knowledge of hygiene and hygienic; business bookkeeping; packaging herbal products and herbal grinding machine which is an average of 42% (in the SME I) and 49% (in SME II). Improved skills about: business bookkeeping; packaging herbal medicine and  use of the machine tool by an average of 41.8% (in the SME I) and 41.6% (in SME II). 2) Based on the evaluation of production, in the SME I with the help of a machine tool there is increased production of flour milling medicinal average of 38.54%. In the SME II, with counseling and assistance labeled plastic, packaging bags models boiled herbs and spices grinding machine there is an increase in the marketing of herbal medicinal flour: 57.97%, boiled herbs marketing model of bag 38% and 64.4% herbal spice mill.